Effects of Oral Ginger Supplementation on the INR - Daniel Rubin; Vishal Patel; Eric Dietrich (Case Reports in Medicine)
Although there are competing options for anticoagulation, many Americans remain on warfarin. Concurrently, the use of alternative medicines is on the rise. With that, the potential for interactions between them is increasing. Ginger has gained popularity in its use. The literature has sparse recent information about the potential conflict between warfarin and ginger. This brief case report discusses the potential scope of the problem as well as the proposed pharmacokinetic and pharmacodynamic interactions between these two commonly used agents.